Analisis Minat Masyarakat Desa Kaballangang Dalam Menggunakan Produk Perbankan Syariah - Riza Syaripuddin; Wahyuni; Desy Arum Sunarta (Mappideceng:Jurnal Ekonomi Syariah, 2025)
Banks have an important role in the economy, including production, consumption, trade, savings and investment activities. In general, banks are divided into conventional banks and sharia banking. These two types of banks have the main function of collecting funds and distributing funds.This study aims to analyze the interest of the Kaballangang Village community in using Islamic banking products and the factors that influence it. The method used is descriptive qualitative with interview, observation, and documentation techniques. The subjects of the study were people who had or did not have experience using Islamic banking products.The research results show that: 1) The Kaballangang Village Community's understanding of sharia banking is still very limited. Most respondents do not have sufficient knowledge regarding sharia banking principles, systems and products. 2) The Kaballangang Village community's interest in sharia banking products is relatively low. Of the 15 informants interviewed, only 3 people used sharia banking products, while the other 12 preferred conventional banks such as BRI.